Influencia del soporte familiar en el desarrollo de habilidades sociales de los niños con discapacidad en el programa de intervención temprana en educación especial PRITE-EE del hospital regional docente de Trujillo, año 2016. - Atoche Castillo, Sandra Gisela (2017)
The present report is intended to analyze the influence of family support in the development of social skills of children with disabilities in the Early Intervention Program in Special Education Killer Rat-EE of the Regional Teaching Hospital in Trujillo, year 2016. The population is constituted by 44 children, belonging to the Program Killer Rat-E of the Regional Teaching Hospital in Trujillo, with which they have applied the methods and techniques of qualitative and quantitative research. In the present investigation, working with parents, because children suffer from disabilities, therefore, a survey was applied to know the different situations of the family with regard to the child, situations at the affective level, health, education, as well as know the various views of the family with a child with a disability. It has been determined that there is a positive influence of the family support in the development of social skills of children with disabilities in the Early Intervention Program in Special Education Killer Rat-EE of the Regional Teaching Hospital in Trujillo.